The optimal monetary policy response to exchange rate misalignments - Wren-Lewis, S; Leith, C (University of Oxford, 2007)
A common feature of exchange rate misalignments is that they produce a divergence between traded and non-traded goods sectors, leading to pressures on monetary policy makers to react. In this paper we develop a small open economy model which features traded and non-traded goods sectors with which to assess the extent to which monetary policy should respond to exchange rate misalignments. To do so we initially contrast the efficient outcome of the model with that under flexible prices and find that the flex-price equilibrium exhibits an excessive exchange rate appreciation in the face of a positive UIP shock. By introducing sticky prices in both sectors we provide a role for policy in the face of UIP shocks. We then derive a quadratic approximation to welfare which comprises quadratic terms in the output gaps in both sectors as well as sectoral rates of inflation. These can be rewritten in terms of the usual aggregate variables, but only after including terms in relative sectoral prices and/or the terms of trade to capture the sectoral composition of aggregates. We derive optimal policy analytically before giving numerical examples of the optimal response to UIP shocks. Finally, we contrast the optimal policy with a number of alternative policy stances and assess the robustness of results to changes in model parameters.